WEIGHTING HEALTH STATES AND STRONG EVALUATION - Edgar, Andrew (Bioethics, 1995)
The problem of public consultation over the allocation of health care resources is addressed by considering the role that quality of life measures, such as QALYs and the Nottingham Health Profile, could play. Such measures are typically grounded in social surveys, and as such may reflect public preferences for health care priorities. Using Charles Taylor's concepts of “weak” and “strong” evaluation, it is suggested that current quality of life measures are inadequate, insofar as they typically presuppose that survey respondents are mere “weak evaluators”, who express only inarticulate preferences. Respondents may, conversely, be understood as strong evaluators, with deeper visions of human nature and the good life informing their health preferences. Space is then created for such respondents to be asked to defend their preferences, and so be encouraged to reflect critically and publicly on the beliefs and prejudices that ground their view of health care priorities.